Peningkatan Kinerja UMKM Donat Tuasan melalui Pengelolaan SDI dan Digitalisasi Penjualan - Afni Haryanti Harahap; Leni Shofiyani; Servina Rahayu; Zainarti Zainarti (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This study aims to understand the influence of human resource management (SDI) and sales digitalization on improving the performance of MSMEs, especially in the donut business in the Tuasan area. According to the results of interviews and direct observations, Donat Tuasan MSMEs face major obstacles in the use of digital technology, such as low digital literacy and lack of understanding of digital payment systems such as QRIS and food delivery service platforms such as GoFood and GrabFood. In an effort to improve business performance, human resource empowerment is very necessary, including education on the use of digital technology and the development of business actors' competencies in managing businesses in a modern manner. The implementation of a cashless payment system and the use of digital platforms are expected to be able to expand market reach, increase transaction efficiency, and improve the competitiveness of MSMEs in the digital era. This study emphasizes that the success of MSME digital transformation is highly dependent on effective SDI management and continuous support from various related parties.